Mechanisms of Sound to Engage Reality : an Insight into Synthesis, Site-Specific Composition, and Fleshy Listening - José Luis Alexander Anderson Esquivel 1994- (2022)
This work aims to invite the reader to reflect on how to carry out a sound composition practice maintaining a global vision that cares for its environment, that embraces diversity and recognizes its neighbor, and that does not reinforce colonial practices or unbalanced power dynamics. By analyzing the work of three Nordic composers whose practices maintain similarities to each other, the author provides evidence of mechanisms of action for care and diversity. At the same time, it provides specific technical resources that can be used to convey these messages. As a composer, Sondre Pettersen (Norway) embodies a compositional, performative practice. Pettersen’s personal relationship with the Sámi community attributes to his work a layer of depth and social representation that leads to dignification and empowerment of an Indigenous community. Originating from Sweden, Maria W. Horn’s compositional practice investigates the architectural qualities of site-specific composition, the stories behind the spaces we inhabit, and the impact of sound on psychology and human perception. Finally, the interdisciplinary artist Halla Steinunn Stefánsdóttir (Iceland) combines the agencies of curator, composer, and performer. Stefánsdóttir’s work invites us to question the normative relationships with her practice from an ecological perspective that seeks new ways to understand our surroundings based on respect and awareness.